las determinantes internas de la política exterior : un tema descuidado en la teoría de la política exterior - Lasagna, Marcelo (Estudios Internacionales, 1995)
This work aims to highlight the relevance of domestic factors in the formation of foreign policy. Without denying the importance of systemic determinants and recognizing their weight in the external behavior of countries, it is situated in a position that foreign policy theorists have generally neglected: the internal political process of foreign policy. This work focuses mainly on one of the possible domestic perspectives of foreign policy, one that emphasizes the change of political regime. From this approach, it is analyzed to what extent the change of political regime can affect the external behavior of the States and some specific cases are examined, to conclude whether or not it is possible to determine a direct relationship between each particular case of regime change and possible variations in foreign policy.